Elementy teorii bankowej w polskim systemie pieniężnym - Knakiewicz, Zenobia (Wydział Prawa i Administracji UAM, 1978)
The author tries to answer two questions: 1) Whether and to which extent elements of banking theory do exist in Polish monetary system? 2) What are the differences and similarities between theoretical principles of Polish monetary system and banking theory? To answer these questions the author considers at first principles of Polish monetary system, which are formulated in regulations of functions, competence and responsibilities of the National Bank of Poland. The author distinguishes three periods characterized by particular and different regulations. In turn, the author compares specific features of principles of Polish monetary system accepted in the third period with principles of productive credit theory, presented in: Tenth Annual Report of Federal Reserve Board, covering operations for the year 1923, "Guides to Credit Policy". The author states in conclusion, that some features of banking theory exist in Polish monetary system. There occured, however, important modifications of principles accepted for the third period of banking theory, i.e. in productive credit theory, instead of passive transferring that theory into the conditions of a socialist state.
Elements of Banking Theory in Polish Monetary System